Proteome reprogramming of endometrial epithelial cells by human trophectodermal small extracellular vesicles reveals key insights into embryo implantation. Issue 13 (6th May 2021) - Poh, Qi Hui; Rai, Alin; Carmichael, Irena Iśka; Salamonsen, Lois A; Greening, David W
Abstract: Embryo implantation into the receptive endometrium is critical in pregnancy establishment, initially requiring reciprocal signalling between outer layer of the blastocyst (trophectoderm cells) and endometrial epithelium; however, factors regulating this crosstalk remain poorly understood. Although endometrial extracellular vesicles (EVs) are known to signal to the embryo during implantation, the role of embryo‐derived EVs remains largely unknown. Here, we provide a comprehensive proteomic characterisation of a major class of EVs, termed small EVs (sEVs), released by human trophectoderm cells (Tsc‐sEVs) and their capacity to reprogram protein landscape of endometrial epithelium in vitro. Highly purified Tsc‐sEVs (30–200 nm, ALIX +, TSG101 +, CD9/63/81 + ) were enriched in known players of implantation (LIFR, ICAM1, TAGLN2, WNT5A, FZD7, ROR2, PRICKLE2), antioxidant activity (SOD1, PRDX1/4/6), tissue integrity (EZR, RAC1, RHOA, TNC), and focal adhesions (FAK, ITGA2/V, ITGB1/3). Functionally, Tsc‐sEVs were taken up by endometrial cells, altered transepithelial electrical resistance, and upregulated proteins implicated in embryo attachment (ITGA2/V, ITGB1/3), immune regulation (CD59, CD276, LGALS3), and antioxidant activity (GPX1/3/4, PRDX1/2/4/5/6): processes that are critical for successful implantation. Collectively, we provide critical insights into Tsc‐sEV‐mediated regulation of endometrial function that contributes to our understanding of the molecular basis of implantation.